2021
DOI: 10.1177/23259671211031244
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Focal Cartilage Defect Treatments in Middle-Aged Versus Younger Patients

Abstract: Background: Focal cartilage defects are often debilitating, possess limited potential for regeneration, are associated with increased risk of osteoarthritis, and are predictive for total knee arthroplasty. Cartilage repair studies typically focus on the outcome in younger patients, but a high proportion of treated patients are 40 to 60 years of age (ie, middle-aged). The reality of current clinical practice is that the ideal patient for cartilage repair is not the typical patient. Specific attention to cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 85 publications
(262 reference statements)
0
41
0
Order By: Relevance
“…A decline in physical function is a major manifestation of aging, including reduced athletic capacity due to poor cartilage quality. In fact, the natural decline in cartilage performance with advancing age may be a perplexing phenomenon, and chronic age-related cartilage defects in middle-aged patients are perhaps an expression of early osteoarthritis (OA) [ 37 , 38 ]. It is reported that the largest natural decrease of cartilage quality in normative IKDC data occurred between the ages of 51 and 65 years, followed by the decline between the ages of 35 and 50 years [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decline in physical function is a major manifestation of aging, including reduced athletic capacity due to poor cartilage quality. In fact, the natural decline in cartilage performance with advancing age may be a perplexing phenomenon, and chronic age-related cartilage defects in middle-aged patients are perhaps an expression of early osteoarthritis (OA) [ 37 , 38 ]. It is reported that the largest natural decrease of cartilage quality in normative IKDC data occurred between the ages of 51 and 65 years, followed by the decline between the ages of 35 and 50 years [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Unfortunately, due to its avascular nature and scarce cellular content, articular cartilage lesions have a limited ability to self-repair, often leading to osteoarthritis. [3][4][5] Depending on the severity of the damage, different strategies may be adopted to alleviate debilitating pain and restore mobility, delaying the need for a total joint replacement. [4] When pharmacological treatments and physiotherapy are no longer effective, cartilage restoration techniques can be applied, including microfracture, autologous chondrocyte implantation, and osteochondral autograft/allograft transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…The existing treatments for articular cartilage defects include debridement, microfracture, osteochondral autograft transfer, osteochondral allograft, and autologous chondrocyte implantation [ 4 ]. However, these treatments each have limitations and drawbacks.…”
Section: Introductionmentioning
confidence: 99%